Speechwright : an insider's take on political rhetoric - Gavin, William F. (Michigan State University Press, 2011)
For almost thirty years, William F. Gavin wrote speeches at the highest levels of government. Speechwright is his insider's view of politics, a shrewd critique of presidential and congressional rhetoric, and a personal look at the political leaders for whom he wrote speeches. While serving President Richard Nixon and candidate Ronald Reagan, Gavin advocated for "working rhetoric"--Well-crafted, clear, hard-hitting arguments that did not off er visions of the unattainable, but instead limited political discourse to achievable ends reached through practical means. Filled with hard-earned wisdom about politics and its discontents, Speechwright describes Gavin's successes, his failures, and his call for political rhetoric built on strong argument rather than the mere search for eloquence.